2021
DOI: 10.3201/eid2705.210514
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 during Border Quarantine and Air Travel, New Zealand (Aotearoa)

Abstract: The strategy in New Zealand (Aotearoa) to eliminate coronavirus disease requires that international arrivals undergo managed isolation and quarantine and mandatory testing for severe acute respiratory syndrome coronavirus 2. Combining genomic and epidemiologic data, we investigated the origin of an acute case of coronavirus disease identified in the community after the patient had spent 14 days in managed isolation and quarantine and had 2 negative test results. By combining genomic sequence analysis and epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 14 publications
0
85
1
1
Order By: Relevance
“…However, this was one of 13 cases not sequenced, and quarantine hotel information was missing for 15 cases in total (n=15/59, 25.4%). Given that instances of SARS-CoV-2 transmission among epidemiologically unlinked cases during quarantine have been documented 15 , we cannot conclusively determine whether transmission occurred in transit or quarantine.…”
Section: Resultsmentioning
confidence: 99%
“…However, this was one of 13 cases not sequenced, and quarantine hotel information was missing for 15 cases in total (n=15/59, 25.4%). Given that instances of SARS-CoV-2 transmission among epidemiologically unlinked cases during quarantine have been documented 15 , we cannot conclusively determine whether transmission occurred in transit or quarantine.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports suggest that aerosol transmission is indeed a nonnegligible mode of SARS-CoV-2 transmission and that respirator masks may provide additional protection compared to surgical masks. [17][18][19]21,22 On the other hand, single case reports have suggested that surgical masks are equivalent to respirators in protecting HCW from SARS-CoV-2 infection. 23,24 These supposedly contradictory findings can be reconciled when considering a particular feature of SARS-CoV-2, namely its high overdispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar incident occurred at a managed isolation and quarantine facility in Christchurch, New Zealand. 13 In the Christchurch event, the genomic and epidemiological data suggested that an initial transmission event happened between two quarantined rooms during a brief 50-second gap of door opening between two quarters into the shared corridor. This incident resulted in two known transmission events outside the facility in New Zealand.…”
Section: Discussionmentioning
confidence: 99%